High ammonia sensitive ability of novel Cu12Sb4S13 quantum dots@reduced graphene oxide nanosheet composites at room temperature - Liu, Yueli; Sang, Binghua; Wang, Haoran; Wu, Zijing; Wang, Yuxuan; Wang, Ziwei; Peng, Zhuoyin; Chen, Wen (Chinese chemical letters, 2020)
Schematic diagram of the gas sensing mechanism and performance of Cu12Sb4S13 quantum dots@rGO composites towards NH3 at room temperature. [Display omitted] •Novel Cu12Sb4S13 QDs@rGO composites are successfully prepared via solvent thermal method.•The composites exhibit excellent responses towards NH3 at room temperature with a detection limit of 1 ppm.•The composites possess an excellent stability during the humidity range of 45 %–80 % and a quite high selectivity towards ammonia. In the work, rGO nanosheet is synthesized using the typical Hummer’s method, then Cu12Sb4S13 quantum dots@rGO composites are prepared by solvent thermal method, and Cu12Sb4S13 quantum dots with the average size of 5 nm are densely distributed on the surface of rGO sheet. NH3 gas response of Cu12Sb4S13 quantum dots@rGO nanosheet composites at room temperature of 25 °C is enhanced compared with the pure Cu12Sb4S13 quantum dots and rGO nanosheet, and the composites possess an excellent stability during the humidity range of 45%–80% with a low detection limit of 1 ppm, which is related with the intrinsic hydrophobicity characteristic of Cu12Sb4S13 quantum dots. It also proves that Cu12Sb4S13 quantum dots@rGO nanosheet composites have a quite high selectivity towards ammonia compared with ethanol, methanol, acetone, toluene, hydrogen sulfide and nitrogen dioxide at room temperature. The gas sensing mechanism of the composites is discussed primarily.